Remarkable Presentation: Anaplastic Thyroid Carcinoma Arising from Chronic Hyperthyroidism - Habib G. Zalzal; Jeffson Chung; Jessica A. Perini (Case Reports in Endocrinology)
Background. Undifferentiated anaplastic carcinoma rarely develops from chronic hyperthyroidism. Although acute hyperthyroidism can develop prior to anaplastic transformation, chronic hyperthyroidism was thought to be a protective measure against thyroid malignancy. Methods. A 79-year-old female presented acutely to the hospital with dyspnea. She had been taking methimazole for chronic hyperthyroidism due to toxic thyroid nodules, previously biopsied as benign. Upon admission, imaging showed tracheal compression, requiring a total thyroidectomy with tracheostomy for airway management. Results. Pathology demonstrated undifferentiated anaplastic thyroid carcinoma. The patient passed away shortly after hospital discharge. Despite treatment with methimazole for many years, abrupt enlargement of her toxic multinodular goiter was consistent with malignant transformation. Chronic hyperthyroidism and toxic nodules are rarely associated with thyroid malignancy, with only one previous report documenting association with anaplastic thyroid carcinoma. Conclusion. Progressive thyroid enlargement and acute worsening of previously controlled hyperthyroidism should promote concern for disease regardless of baseline thyroid function.